2013
DOI: 10.4049/jimmunol.1201044
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Controls the Innate Immune Response against Listeria monocytogenes via Classical IL-6 Signaling

Abstract: The cytokine IL-6 plays a protective role in immune responses against bacterial infections. However, the mechanisms of IL-6–mediated protection are only partially understood. IL-6 can signal via the IL-6R complex composed of membrane-bound IL-6Rα (mIL-6Rα) and gp130. Owing to the restricted expression of mIL-6Rα, classical IL-6 signaling occurs only in a limited number of cells such as hepatocytes and certain leukocyte subsets. IL-6 also interacts with soluble IL-6Rα proteins and these IL-6/soluble IL-6Rα comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 59 publications
6
107
0
1
Order By: Relevance
“…We showed how targeting site IIb of IL-6R would be favorable to inhibit an exacerbated IL-6-induced response, here measured by SAA induction typically associated with a cis-mediated event (30). The injection of anti-IL-6R mAbs to mice when IL-6 serum levels were maximal showed that 25F10 significantly reduced the IL-6-driven SAA response.…”
Section: Discussionmentioning
confidence: 95%
“…We showed how targeting site IIb of IL-6R would be favorable to inhibit an exacerbated IL-6-induced response, here measured by SAA induction typically associated with a cis-mediated event (30). The injection of anti-IL-6R mAbs to mice when IL-6 serum levels were maximal showed that 25F10 significantly reduced the IL-6-driven SAA response.…”
Section: Discussionmentioning
confidence: 95%
“…60 Antibodies were applied in doses previously shown to be effective, including anti-IL-6R (750 mg, MR16-1; provided by Chugai Pharmaceutical Co. Ltd., Tokyo, Japan 33 ), anti-IL-6 (500 mg, MP5-20F3), and sgp130Fc (250 mg), 61 or control antibodies (750 mg rat IgG for MR16-1 or 500 mg hIgG for anti-IL-6 and sgp130Fc) were intraperitoneally injected 24 hours before and 5 days after NTN induction. For aNTN, 41 mice were preimmunized with sheep IgG in complete Freund's adjuvant at day 5.…”
Section: Animal Experiments and Functional Studiesmentioning
confidence: 99%
“…4) [62]. Interestingly we found in animals that the defense of the organism from bacterial infections depends on the membrane bound IL-6R and is not compromised when only IL-6 trans-signaling is blocked [63,64]. This has consequences for the therapeutic blockade of cytokines.…”
Section: Specific Blockade Of Il-6 Trans-signalingmentioning
confidence: 94%